Microarray Analysis of lncRNA and mRNA Reveals Enhanced Lipolysis Along With Metabolic Remodeling in Mice Infected With Larval Echinococcus granulosus - Lu, Yang; Liu, Hua; Yang, Xiao-ying; Liu, Jia-xue; Dai, Meng-yu; Wu, Jia-cheng; Guo, Yu-xin; Luo, Tian-cheng; Sun, Fen-fen; Pan, Wei (Frontiers in Physiology, 2020)
Parasitic infection improves metabolic homeostasis in “western diet” induced-obesity, which partially results from the regulation of adipogenesis. However, the underlying mechanism remains largely unknown. This study investigated the long non-coding RNA（lncRNA）and mRNA profiles of subcutaneous adipose tissues in mice infected by the protoscoleces of Echinococcus granulosus (EgPSC) using a microarray analysis. In comparison with control mice, the infected mice showed decreased mass of adipose tissues and shrunken size of adipocytes. The indirect calorimetry found the alternation of energy metabolism post infection, which was characterized by less CO2 production and O2 consumption, sharp decline of carbohydrate oxidation and a little increase of fat oxidation. A total of 1,052 mRNAs and 220 lncRNAs were differentially expressed in infected subcutaneous adipose tissues (fold change ≥2, P＜0.05). Of them, 541 mRNAs were upregulated and 511 mRNAs were downregulated; 126 lncRNAs were upregulated and 94 lncRNAs were downregulated. The Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that the parasitic infection reprograms a complex metabolic network. Notably, “lipoxygenase” and “Arginine and proline metabolism” pathways were significantly upregulated while “glycolysis”, “Tricarboxylic acid (TCA) cycle”, “denovo lipogenesis” and “lipid droplet” pathways were dramatically downregulated. In addition, several key lncRNAs were linked with insulin resistance and adipocyte differentiation. Overall, this study suggests that E. granulosus infection inhibits the adipogenesis, which provides a novel insight for metabolic homeostasis mediated by parasitic infection, and hypertrophic adipocytes in obesity.